Correlation between patient‐reported manual ability and three objective measures of upper limb function in people with multiple sclerosis. (28th September 2022) - Solaro, Claudio; Di Giovanni, Rachele; Grange, Erica; Brichetto, Giampaolo; Mueller, Margit; Tacchino, Andrea; Bertoni, Rita; Patti, Francesco; Pappalardo, Angelo; Prosperini, Luca; Castelli, Letizia; Rosato, Rosalba; et al.
Abstract: Background and purpose: Upper limb (UL) function is often affected in people with multiple sclerosis (PwMS) and is typically assessed through objective measures, including the Nine Hole Peg Test (9‐HPT), Box and Block Test (BBT), and Hand Grip Strength (HGS). It is important to include the subjective perspective of PwMS in the assessment. This study aims to evaluate associations between Manual Ability Measure‐36 (MAM‐36) and 9‐HPT, BBT, and HGS in MS. Methods: The cross‐sectional study included five Italian centers. Inclusion criteria were age ≥ 18 years, MS diagnosis, and stable disease course. Exclusion criteria were bilateral UL paralysis, and concomitant orthopedic or neurological diseases. Results: A total of 199 PwMS were included: 128 female, mean age = 50.7 ± 13.0 years, 119 relapsing–remitting MS (RRMS), 31 primary and 49 secondary progressive MS, mean disease duration = 14.0 ± 10.4, years, mean Expanded Disability Status Scale (EDSS) = 4.6 ± 2.0. The MAM‐36 showed small correlations with 9‐HPT, BBT, and HGS. Correlations between MAM‐36 and 9‐HPT and BBT were highest among subjects with EDSS ≥ 6 and progressive MS. MAM‐36 and HGS showed the highest correlations in subjects with EDSS ≤ 5 and RRMS. Combining 9‐HPT and HGS provided the strongest predictive power over the MAM‐36. Conclusions: Correlations between objective measures and MAM‐36 were small to moderate, meaning that objective measures do not match subjects' perception of UL function. The combination of 9‐HPT and HGS measures can help improve the assessment of UL function in activities of daily living.